Single-Cell RNA Sequencing Revealed CD14+ Monocytes Increased in Patients With Takayasu’s Arteritis Requiring Surgical Management - Qing, Gao; Zhiyuan, Wu; Jinge, Yu; Yuqing, Miao; Zuoguan, Chen; Yongpeng, Diao; Jinfeng, Yin; Junnan, Jia; Yijia, Guo; Weimin, Li; Yongjun, Li (Frontiers in Cell and Developmental Biology, 2021)
Objectives Takayasu Arteritis (TA) is a highly specific vascular inflammation and poses threat to patients’ health. Although some patients have accepted medical treatment, their culprit lesions require surgical management (TARSM). This study aimed at dissecting the transcriptomes of peripheral blood mononuclear cells (PBMCs) in these patients and to explore potential clinical markers for TA development and progression. Methods Peripheral blood were collected from four TA patients requiring surgical management and four age-sex matched healthy donors. Single cell RNA sequencing (scRNA-seq) was adopted to explore the transcriptomic diversity and function of their PBMCs. ELISA, qPCR and FACS were conducted to validate the results of the analysis. Results A total of 29918 qualified cells were included for downstream analysis. Nine major cell types were confirmed, including CD14+ monocytes, CD8+ T cells, NK cells, CD4+ T cells, B cells, CD16+ monocytes, megakaryocytes, dendritic cells and plasmacytoid dendritic cells. CD14+ monocytes (50.0% vs 39.3%, p<0.05) increased in TA patients, as validated by FACS results. CD163 may serve as a potential clinical marker, as it also increased in TA patients. Some ILs like IL-6, IL-6STP1, IL-6ST, IL-15, and IL-15RA increased in TA group but the underlying mechanism remained to be further elucidated in the future. Conclusion Transcriptome heterogeneities of PBMCs in TA patients requiring surgical management were revealed in the present study. In these patients with TA, CD14+ monocytes were increased and activated, indicating a new treatment and study direction in this field.